Pennies from haven: Wages and profit shifting - Annette Alstadsæter; Julie Brun Bjørkheim; Ronald B. Davies; Johannes Scheuerer (University College Dublin, UCD School of Economics, 2022)
Increasing attention has been given to the fact that some multinational enterprises shift income to tax haven countries, an activity that generates inequality in corporate taxation. Here, we examine how profit shifting relates to wage inequality. Using rich matched employer-employee data from Norway, we find that profit-shifting firms pay higher wages, particularly among service firms where the wage premium is approximately 2%. Furthermore, this average effect masks significant within-firm heterogeneity with high-skill occupations - and managers in particular - earning higher shifting wage premiums. CEOs particularly gain, with their wages rising nearly 10%. These results thus suggest that profit shifting by multinationals meaningfully contributes to wage inequality, both between and within firms. Finally, our back-of-the-envelope calculations suggest these higher wages would generate additional income tax revenues which would offset around 3% of the fall in Norway's corporate tax revenues due to profit shifting
Keywords: F23; H26; J31; J32; M12; 330; Profit Shifting; Tax Haven; Tax Avoidance; Multinational Firms; Wage Distribution; Inequality